심해용 무인 잠수정의 동역학 계수의 추정에 관한 연구 - 백혁(HYUK BAEK); 김기훈(KI-HUN KIM); 전봉환(BONG-HUAN JUN); 이판묵(PAN-MOOK LEE); 임용곤(YONG-KON LIM) (Han-guk haeyang gonghak hoeji (Online), 2008)
This paper represents the experimental identification of a finite-dimensional dynamical plant model for the HEMIRE Remotely Operated Vehicle. The experiments were conducted during sea trials in the East Sea in October 2006 and peer testing by the South Sea Research Institute in January 2007. A least-squares method was employed to identify decoupled single degree-of-freedom plant dynamical models for the X, Y, Z and heading degree-of-freedom from experimental data. The performance of the identified plant dynamical model was evaluated by directly comparing simulations of the identified plant model to the experimentally observed motion data from the actual vehicle.